Quantification and determinants of the amount of respiratory syncytial virus (RSV) shed using real time PCR data from a longitudinal household study [version 1; referees: 2 approved, 1 approved with reservations] - Miriam Wathuo; Graham F. Medley; D. James Nokes; Patrick K. Munywoki (Wellcome Open Research, 2016)
Background A better understanding of respiratory syncytial virus (RSV) epidemiology requires realistic estimates of RSV shedding patterns, quantities shed, and identification of the related underlying factors. Methods RSV infection data arise from a cohort study of 47 households with 493 occupants, in coastal Kenya, during the 2009/2010 RSV season. Nasopharyngeal swabs were taken every 3 to 4 days and screened for RSV using a real time polymerase chain reaction (PCR) assay. The amount of virus shed was quantified by calculating the ‘area under the curve’ using the trapezoidal rule applied to rescaled PCR cycle threshold output. Multivariable linear regression was used to identify correlates of amount of virus shed. Results The median quantity of virus shed per infection episode was 29.4 (95% CI: 15.2, 54.2) log10 ribonucleic acid (RNA) copies. Young age (<1 year), presence of upper respiratory symptoms, intra-household acquisition of infection, an individual’s first infection episode in the RSV season, and having a co-infection of RSV group A and B were associated with increased amount of virus shed. Conclusions The findings provide insight into which groups of individuals have higher potential for transmission, information which may be useful in designing RSV prevention strategies.